Unraveling the properties of sharply defined submicron scale FeCu and FePd magnetic structures fabricated by electrodeposition onto electron-beam-lithographed substrates. (August 2020) - Dislaki, Evangelia; Cialone, Matteo; Celegato, Federica; Rizzi, Paola; Tiberto, Paola; Vadilonga, Simone; Többens, Daniel; Sort, Jordi; Pellicer, Eva
Abstract: In this work, Fe–X (X = Cu, Pd) submicron-scale structures were electrodeposited onto pre-patterned substrates prepared by e-beam lithography. The FeCu and FePd (with reduced Pd content) systems were investigated as attractive candidates for a variety of potential applications in magnetic data storage and biomedicine. Confined growth in the restricted cavities resulted in a nanoscale grain size leading to well-defined geometries with sharp edges and corners and an average height of up to 215 nm. Specifically, nine 100 μm × 100 μm arrays of three geometries (cylindrical, rectangular and cruciform) in three different sizes were created. In addition, the total deposition time ranged from 3.5 s (FeCu) to 200 s (FePd), i.e. much faster than by traditional physical vapor deposition approaches and was performed at ambient conditions. Magnetic force microscopy for the cylindrical and cruciform structures revealed virtually no contrast at zero field, suggesting magnetic curling effects (instead of coherent rotation) during magnetization reversal. These curling effects result in low values of remanent magnetization, which is advantageous in minimizing dipolar interactions between the structures either when they are deposited onto the substrate or eventually dispersed in a liquid (e.g. in biomedical applications, as drug delivery carriers, where particle agglomeration is undesirable). Graphical abstract: Unlabelled Image Highlights: Well-defined FeCu and FePd submicron-scale magnetic structures are prepared by electrodeposition onto e-beam lithographed substrates. Sharply resolved geometries (cylindrical, rectangular and cruciform) are approximately 200 nm in height. The chemical composition and microstructure of the two systems are compared. Magnetic force microscopy for the cylindrical and cruciform structures suggest magnetic curling effects during magnetization reversal.